A platform-based structure for group purchasing with bundles of items. Issue 1 (31st December 2023) - Hasanpour Jesri, Zahra Sadat; Eshghi, Kourosh; Rafiee, Majid
Abstract : Despite the growth of group purchasing, few studies consider group purchasing with bundled products. Generally, an individual buyer may be reluctant to buy a bundle and prefer to buy a portion of it. By group buying, buyers purchase their products with lower price. We proposed a group purchasing structure for bundles of items in which buyers' purchasing power is a function of time and bundles' expiration date. A platform is also considered that charges sellers after selling their bundles. Three strategies are proposed in terms of three problems. In problem (I), a group of buyers wants to buy those products whose bundle price they can pay for in full and maximise their total savings. In problem (II), which is an extension of problem (I), the products' importance is also considered. In problem (III), cohorts of buyers try to buy all their products, and the platform could pay the remaining price of the unsuccessful bundles. Here, the remaining products are in the platform's ownership. Based on the results, while the first strategy accounts for most of buyers' savings, the other two strategies allow more purchases. The highest platform income is for problem (III) due to the possibility of selling additional products.